1994
DOI: 10.1103/physrevc.49.2118
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of neutron densities from elastic proton scattering byPb206,207,208

Abstract: The method for extraction of neutron and matter densities from data on cross sections and spin observables for elastic p-nucleus scattering is presented. The effective nuclear potential was treated to the 6rst order with respect to the t-matrix and density distributions. To eliminate uncertainties associated with the t matrix, the latter has been determined directly from p-Ca scattering data, where the proton and neutron densities are known sufBciently well. The medium modi6cations in the t matrix have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
164
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(174 citation statements)
references
References 52 publications
10
164
0
Order By: Relevance
“…6. Results obtained with the FKVW interaction are compared with data [62] for the Sn isotopes, and with the empirical value of r n − r p in 208 P b (0.20 ± 0.04 fm from proton scattering data [63], and 0.19 ± 0.09 fm from the excitation of the isovector giant dipole resonance by α-scattering [64]). …”
Section: Spherical Nucleimentioning
confidence: 99%
“…6. Results obtained with the FKVW interaction are compared with data [62] for the Sn isotopes, and with the empirical value of r n − r p in 208 P b (0.20 ± 0.04 fm from proton scattering data [63], and 0.19 ± 0.09 fm from the excitation of the isovector giant dipole resonance by α-scattering [64]). …”
Section: Spherical Nucleimentioning
confidence: 99%
“…In particular, he has shown that there is a very strong linear correlation between the neutron skin thickness in 208 Pb and the individual parameters that determine the asymmetry energy S 2 (ρ): a 4 , p 0 and ∆K 0 . The empirical value of the difference between neutron and proton rms radii r n − r p in 208 Pb (0.20 ± 0.04 fm from proton scattering data [34], and 0.19 ± 0.09 fm from the alpha scattering excitation of the isovector giant dipole resonance [35]) places the following constraints In Fig. 4 we plot the asymmetry energy S 2 (ρ) as function of the baryon density for the three steps of our calculation of the nuclear matter EOS: first, using only chiral one-and two-pion exchange calculated in CHPT, next with the inclusion of leading order isoscalar condensate background nucleon self-energies that arise through changes in the quark condensate and the quark density at finite baryon density, and finally with the non-linear contribution δG (1) V to the vector condensate nucleon self-energy.…”
Section: Asymmetric Nuclear Mattermentioning
confidence: 99%
“…The rms radius of neutron densities in nuclei has been measured with hadronic probes such as proton-nucleus elastic scattering [42][43][44][45] or inelastic scattering excitation of the giant dipole and spin-dipole resonances [46,47]. Antiprotonic atoms are helpful to probe the size of the neutron skin of nuclei from the fact that the nuclear periphery is very sensitive to antiprotons in the normally electronic shell.…”
Section: Introductionmentioning
confidence: 99%